Giving back Filipino America and the politics of diaspora giving - Mariano, L. Joyce Zapanta 1973- (Asian American history and culture., 2021)
"Examines Filipino diaspora through the complex of meanings associated with "giving back" and explores the process of diaspora formation. Argues that giving-related institutions and discourse-such as aid, development, altruism, and benevolence-are integral to understanding diaspora formation today"--